THE INFLUENCE OF STRATEGIC LEADERSHIP AND PERCEPTIONS OF ORGANIZATIONAL SUPPORT ON THE JOB SATISFACTION OF BANK INDONESIA EMPLOYEES - Wahyu Defrianda; Naufal Bachri; Yulius Dharma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines how Bank Indonesia workers at the representative offices in Lhokseumawe and Banda Aceh perceive organizational support and its impact on their job satisfaction. 121 respondents provided the primary data that was used in this study. Structural Equation Modeling (SEM) is used in data analysis. The study's findings demonstrate that the work environment perceived organizational support, and strategic leadership all significantly and favorably affect employee job satisfaction. With quasi-moderation as the mode of moderation, the work environment as a moderating variable in this study can effectively moderate the influence between leadership and perceptions of organizational support on employee job satisfaction.